2016
DOI: 10.5897/ajb2016.15213
|View full text |Cite
|
Sign up to set email alerts
|

In vitro regeneration of disease free enset [Ensete ventricosum (Welw) Cheesman] planting materials from bacterial wilt diseased plants using shoot tip culture

Abstract: In vitro regeneration of disease free enset [Ensete

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…Based on these observations, explants were cultured on media supplemented with 5 mg/l BAP (designated as bud induction medium [BIM] for further experiments) for optimal bud induction. Previous studies reported bud induction at lower BAP concentrations (1.5–4.5 mg/l) [18, 19] or in combination with an auxin such as IAA or ABA [19, 20].
Fig.
…”
Section: Resultsmentioning
confidence: 83%
See 3 more Smart Citations
“…Based on these observations, explants were cultured on media supplemented with 5 mg/l BAP (designated as bud induction medium [BIM] for further experiments) for optimal bud induction. Previous studies reported bud induction at lower BAP concentrations (1.5–4.5 mg/l) [18, 19] or in combination with an auxin such as IAA or ABA [19, 20].
Fig.
…”
Section: Resultsmentioning
confidence: 83%
“…Our results agree with previous reports of successful shoot regeneration using media containing either BAP alone or a combination of high BAP with low auxin. Genene and Mekbib [18] reported the development of 20–23 shoots per explant per subculture for different enset cultivars cultured on media having 4.5–6 mg/l BAP and 2 mg/l NAA. In this study SEM4 media with 2 mg/l BAP (hereafter referred to as SEM) was identified as the most ideal for shoot regeneration and elongation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Plants propagated by cuttings also show a lower longevity and possess a lower drought and disease resistance than those propagated by seeds (Sujatha et al, 2005). Again this conventional propagation technique has its own draw back since planting materials are one of sources for disease transmission from place to place (Genene, 2014). Besides, for an effective large scale commercialized production of Jatropha maintaining true to type genotypes, producing disease free planting materials and high number of propagule in vitro culture has a paramount importance.…”
Section: Introductionmentioning
confidence: 99%